(untitled) (Journal of Information and Communication Technology, 2022)
This paper proposes a Generalised Stochastic Petri net (GSPN) model representing a generic e-procurement workflow process. The model displays the dynamic behaviour of the system and shows the inter relationship of process activities. An analysis based on matrix equation approach enabled users to analyse the critical system’s states, and thus justify the process performance. The results obtained allow users for better decision making in improving e-procurement workflow performance.